Cooperation between international organizations: Demand, supply, and restraint - Diana Panke; Sören Stapel (The Review of International Organizations, 2023)
Regime complexity characterizes the international system, as many international organizations (IOs) overlap in membership and competencies at the same time. Unmanaged overlaps endanger the effectiveness of IOs. Inter-organizational cooperation can mitigate such negative consequences. However, a novel dataset reveals that not all overlapping IOs cooperate with each other and the institutionalization of cooperation agreements varies. Why do some but not all overlapping IOs opt for cooperation agreements, and why do their designs vary? The analysis of a demand–supply–restraint model shows that increased exposure to overlaps creates a demand for IOs to reach cooperation agreements and for their strong institutionalization. States respond more favourable to the supply of cooperation agreements when they are used to international cooperation and internal authority-delegation. The restraint component underscores that IOs are less inclined to cooperate when ideological differences and power differentials between them are greater and that IOs choose highly institutionalized cooperation agreements when their ideological differences are limited.
Keywords: 320; Regime complexity; International organizations; Overlap; Negative externalities; Interorganizational cooperation; Design of cooperation agreements; Demand–supply restraint model; Comparative analysis